2023
DOI: 10.21037/tcr-23-449
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine reader IGF2BP3 as a prognostic Biomarker contribute to malignant progression of glioma

Abstract: Background: Glioblastoma (GBM) is a highly aggressive cancer having a dismal prognosis. N 6methyladenosine (m 6 A) is closely related to GBM progression. The significance of m 6 A modifications depends on the m 6 A readers, whose functions in glioma progression are largely unknown. This study sought to investigate the expression of the m 6 A related gene in glioma and its effect on the malignant progression of glioma.Methods: The expression differences between low-grade gliomas (LGGs) and high-grade gliomas (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Univariate analysis revealed that high expression of METTL14, RBM15, ZC3H13, WTAP, FTO, ALKBH5, YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2, IGF2BP2, and IGF2BP3 was associated with an unfavorable prognosis for gliomas. Furthermore, multivariate Cox regression analysis indicated that high expression of YTHDC2 served as an independent positive prognostic factor for overall survival, while elevated expression of IGF2BP3 acted as an independent negative prognostic factor for the overall survival of glioma patients [26].…”
Section: A Rna Modification and Associate Proteins As Prognostic Biom...mentioning
confidence: 97%
See 4 more Smart Citations
“…Univariate analysis revealed that high expression of METTL14, RBM15, ZC3H13, WTAP, FTO, ALKBH5, YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2, IGF2BP2, and IGF2BP3 was associated with an unfavorable prognosis for gliomas. Furthermore, multivariate Cox regression analysis indicated that high expression of YTHDC2 served as an independent positive prognostic factor for overall survival, while elevated expression of IGF2BP3 acted as an independent negative prognostic factor for the overall survival of glioma patients [26].…”
Section: A Rna Modification and Associate Proteins As Prognostic Biom...mentioning
confidence: 97%
“…In gliomas, the expression levels of METTL3, ALKBH5, YTHDF2, and IGF2BP3 were found to be elevated compared to normal brain tissues [19][20][21][22][23][24][25][26]. Furthermore, the individual expression level of each protein is indicative of a poor prognosis in malignant glioma patients [19][20][21][22][23][24][25][26].…”
Section: A Rna Modification and Associate Proteins As Prognostic Biom...mentioning
confidence: 99%
See 3 more Smart Citations